Design and development of mountain bike rear suspension for all mountain riding style - Mohd Aiman, Mahusin (2013)
This report discuss about the design and development of mountain bike rear suspension for all-mountain riding style. The objective of this study is to design and develop a proper geometry of rear suspension system for mountain bike, and to study the motion mechanisms of rear suspension system. This study deals with the path analysis (PA) of a wheel axle and pivot position determination for the crank set of mountain bike. The results show that the new developed rear suspension base on Monolink type have a suitable frame geometry that give a great horizontal and vertical travel for improvement of pedalling efficiency. In addition the crank set position for the Monolink rear suspension also helping for a smooth ride resulting from the less chain growth and chainstay lengthening. These research uses AutoCAD, Autodesk Sketch Pro and SolidWork to design and analyze the path analysis in terms of displacement of “x” and “y” axis of the developed rear suspension. The results are compared between another several types of rear suspension mechanisms.